2021
DOI: 10.1101/2021.10.07.463529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shiitake mycelium fermentation improves digestibility, nutritional value, flavor and functionality of plant proteins

Abstract: Plant proteins can serve as inexpensive and environmentally friendly meat-replacements. However, poor taste characteristics and relatively low nutritional value prevent their full acceptance as meat substitutes. Fermentation of food has been historically used to improve the quality of foods. In this work we describe the improvement in digestibility, nutritional value, physical properties, and organoleptic characteristics, of a pea and rice protein concentrate blend through fermentation with shiitake mushroom … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Feed digestibility is positively correlated with the absorption rate of nutrients absorbed by animals and the quality of feed, which was very important for the growth and development of ruminants . Relevant research has demonstrated that fermenting feed could increase the utilization rate of feed (Kawamoto et al, 2009) and the incorporation of white-rot fungi and enzymatic bacteria in diets could improve feed quality and digestibility (So et al, 2020;Clark et al, 2022). In this study, the incorporation of 30% FVMR in diets of Guizhou black male goats could increase the apparent digestibility of DM, CP, and NDF.…”
Section: Effects Of Growth Performance and Apparent Digestibilitymentioning
confidence: 79%
“…Feed digestibility is positively correlated with the absorption rate of nutrients absorbed by animals and the quality of feed, which was very important for the growth and development of ruminants . Relevant research has demonstrated that fermenting feed could increase the utilization rate of feed (Kawamoto et al, 2009) and the incorporation of white-rot fungi and enzymatic bacteria in diets could improve feed quality and digestibility (So et al, 2020;Clark et al, 2022). In this study, the incorporation of 30% FVMR in diets of Guizhou black male goats could increase the apparent digestibility of DM, CP, and NDF.…”
Section: Effects Of Growth Performance and Apparent Digestibilitymentioning
confidence: 79%